Catch and release: evaluating the safety of non-fatal heroin overdose management in the out-of-hospital environment. (2nd November 2018) - Stam, Nathan C.; Pilgrim, Jennifer L.; Drummer, Olaf H.; Smith, Karen; Gerostamoulos, Dimitri
Abstract: Background: The aim of this study was to investigate the safety of the management of non-fatal heroin overdose in the out-of-hospital environment; irrespective of whether or not naloxone had been administered. Heroin toxicity-related deaths as well as heroin intoxication-related traumatic deaths following patient-initiated refusal of transport were investigated. Methods: Heroin-related deaths in the state of Victoria, Australia between 1 January 2012 and 31 December 2013 were investigated and data linkage to pre-hospital Emergency Medical Services performed, in order to identify whether the death was related to the last episode of care by paramedics. The number of non-fatal heroin overdose events over the study period were also examined. Results and discussion: There were a total of 3921 heroin-related attendances by paramedics during the study period, including 2455 cases that involved treatment but where the patient was not transported to hospital. There were also 243 heroin-related deaths identified over the study period and 93% ( n  = 225) of those cases were matched with Ambulance Victoria electronic patient care records. Data linkage revealed 31 heroin-related deaths where there had been a recent presentation with a non-fatal heroin overdose to paramedics; however, none of these deaths were related to that episode of care, including for 11 individuals that were treated on scene by paramedics but not transported to the hospital. Conclusions: This study demonstrated that the treatment of uncomplicated heroin overdose in the out-of-hospital environment was safe in terms of mortality, irrespective of whether or not naloxone had been administered. In all of the non-fatal heroin toxicity cases attended by paramedics, whether or not transported to hospital, death occurred as a result of a subsequent and unrelated heroin overdose.